Pancreatic β-cell mass in European subjects with type 2 diabetes - Rahier, J; Guiot, Y; Goebbels, R.M; Sempoux, C; Henquin, J.C (Diabetes, obesity & metabolism, 2008)
Decreases in both β-cell function and number can contribute to insulin deficiency in type 2 diabetes. Here, we quantified the β-cell mass in pancreas obtained at autopsy of 57 type 2 diabetic (T2D) and 52 non-diabetic subjects of European origin. Sections from the body and tail were immunostained for insulin. The β-cell mass was calculated from the volume density of β-cells (measured by point-counting methods) and the weight of the pancreas. The pancreatic insulin concentration was measured in some of the subjects. β-cell mass increased only slightly with body mass index (BMI). After matching for BMI, the β-cell mass was 41% (BMI < 25) and 38% (BMI 26-40) lower in T2D compared with non-diabetic subjects, and neither gender nor type of treatment influenced these differences. β-cell mass did not correlate with age at diagnosis but decreased with duration of clinical diabetes (24 and 54% lower than controls in subjects with <5 and >15 years of overt diabetes respectively). Pancreatic insulin concentration was 30% lower in patients. In conclusion, the average β-cell mass is about 39% lower in T2D subjects compared with matched controls. Its decrease with duration of the disease could be a consequence of diabetes that, with further impairment of insulin secretion, contributes to the progressive deterioration of glucose homeostasis. We do not believe that the small difference in β-cell mass observed within 5 years of onset could cause diabetes in the absence of β-cell dysfunction.